Analisa Standar Keamanan terhadap Keselamatan Penerbangan di Bandar Udara Komodo Labuan Bajo - Susanto, Agus; Sutrisno, Agus (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
The provision of flight information service by a form of Aerodrome Flight Information Service Information Service and Alerting Service to aircraft should be able to ensure the safety and smooth flow of air traffic in the region. It was also to achieve the purpose of the flight information service it self, namely to prevent collisions between aircraft; aircraft movement areas (manoeuvring area) or beween aircraft with obstacle (obstractions) in the area; and accelerate and maintain the smooth flow of air traffic. Regulation has set some non-public areas in airports that must be kept sterile from activities outside of airport. This is because the area is directrly relate to flight operations. Labuan Bajo Komodo Airport is located near the residential area, so that in conducting flight information service should pay attention to correct condition that will be used airside aircraft. There are some gaps in the fance are used by people as the driveway in order to cross the runway. This is certainly very dangerous because if left unchecked, can occur and trigger a runway incursion accident and incident. Thus, the results of research that has been done on the airport Komodo, repair fences and additional security personnel greatly affect the safety of air traffic. It should also be supported by the community’s understanding of the rules to flight safety